Design of a high-efficiency brushless wound rotor synchronous machine with reduced torque ripple employing a novel stator winding scheme - Muhammad Ahsan ul Haq; Haroon Farooq; Rehan Liaqat; Zafar A. Khan; Abdullah Altamimi (PLoS ONE, 2026)
This paper presents a novel configuration of a brushless wound rotor synchronous machine (BLWRSM). In the proposed configuration, the stator incorporates a specially designed winding having two series-connected sections with unequal numbers of turns. This unique stator winding (SW) scheme generates an additional subharmonic component (SHC) in the stator magnetomotive force (sMMF), which facilitates brushless excitation of the rotor. The rotor includes a field winding (FW) and a harmonic winding (HW), which are connected through an embedded diode bridge rectifier. The SHC in the sMMF produces an alternating voltage in the HW. This alternating voltage is subsequently rectified to direct current (DC) for exciting FW to realize brushless operation. The proposed configuration, employing a unique SW scheme, is evaluated for an 8-pole, 12-slot BLWRSM using two-dimensional finite element analysis in JMAG Designer. The simulation results validate the proposed concept. In comparison with the existing BLWRSM design, the proposed BLWRSM delivers 4.85% higher output power and 4.9% more average torque while using 50.5% lower input current. Unlike conventional BLWRSM topologies requiring dual inverters, the proposed machine operates with a single three-phase inverter and exhibits 0.69% torque ripples. Due to its brushless and spark-free design, the proposed configuration is well-suited for applications in fire-hazard environments such as aircraft systems and the oil and gas industry.